Article 153 Of the Federal Constitution: Governing Principle for Affirmative Policy Against Social Injustice - Wan Ahmad Fauzi, Wan Husain (Universiti Malaysia Pahang, 2021)
The special position of Malays and natives of Sabah and Sarawak remains a national debate despite the fact that its position has been lawfully accorded according to Article 153, Federal Constitution. Those who had significantly benefitted from the implementation of policies under Article 153 among non-Malays and non-natives of Sabah and Sarawak, especially from an economic policy, have yet turned up to defend many allegations thrown at the Government. As a matter of fact, many Malays themselves admitted that the Government had introduced many good programs to elevate the living standard of their community but yet to see much improvement across the country. On the contrary, the wealth accumulated by non-Malays as well as non-natives of Sabah and Sarawak beyond RM1 billion personal net worth as shown in many popular magazines has proven to increase both in the number of individuals and its value. Hence, this paper aims to examine Article 153 and its governance on policies for affirmative action against social injustice using historical and legal analysis methods. The findings in this study could justify the position of Article 153 and allegations against it.